PENGARUH PROFITABILITAS, LEVERAGE DAN STRUKTUR KEPEMILIKAN TERHADAP AGRESIVITAS PAJAK - Giawan Nur Fitria; Ersalina Asmarani (Jurnal Kewirausahaan Bukit Pengharapan, 2021)
This research is the influence of profitability, leverage and ownership structure on tax aggressiveness (empirical study on manufacturing companies in the consumer goods industry registered on the Indonesia Stock Exchange in 2016-2019). This research aims to know the influence of profitability, leverage, and ownership structure as independent variables on tax aggressiveness as the dependent variable. This research uses secondary data financial statements of manufacturing companies in the consumer goods industry registered on the Indonesia Stock Exchange website www.idx.co.id. The population of this research are manufacturing companies in the consumer goods industry registered on the Indonesia Stock Exchange in 2016-2019. Sample by using purposive sampling method, the sample used consisted of 17 companies over a period of 4 years with total of data used are 68 sample data. Data analysis technique used in this research is multiple linear regression analysis. The results of this research indicate that: (1) profitability has a positive effect on tax aggressiveness, (2) leverage has a positive effect on tax aggressiveness, (3) ownership structure has no effect on tax aggressiveness.